Social Media and Sports: Engagement For Sports Fans - Muhamad Chaerul Ichsan; Heny Setyawati; Fajar Awang (Journal of Physical Education and Sports, 2022)
Sports fans develop distinct and interesting relationships with their favorite sports teams, both in person and virtually. However, research on sports fan engagement is still limited in relation to social media. The purpose of this study was to understand why and how sports fans engage with sports athletes/teams on social media. A quantitative descriptive approach was used in this study with the help of questionnaires distributed through social media to 455 respondents. The sample techniques used are purposive sampling and snowball sampling. Researchers distributed the questionnaire through a google form with the help of social media and obtained as many as 394 respondents with the criteria of active social media users and sports fans. The results obtained in this study are mostly respondents are male and aged between 21 to 30 years. They are more active on social media every day with an intensity of 2 to 5 hours every day. People prefer social media as a medium to interact with their favorite sports athletes/teams. The conclusion in this study is that athletes or sports teams must develop the use of their social media as their marketing tool and become a liaison facility between athletes or sports teams and sports fans.